EFFICACY AND SAFETY OF COMBINED ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH RENOPARENCHYMAL ARTERIAL HYPERTENSION IN ACTUAL CLINICAL PRACTICE - N. J. Borovkova; N. N. Borovkov; T. I. Maslov (Столичная издательская компания, 2016)
Aim. To evaluate efficacy and safety of combined antihypertensive therapy based on ramipril, metoprolol tartrate, amlodipine bensilate and rilmenidine dihydrogen phosphate in hypertensive patients with chronic glomerulonephritis (CGN) and normal renal function. Material and methods. 136 patients (39,2±14,6 y.o.) with hypertensive type of primary CGN and with normal renal function were examined. Clinical blood pressure (BP) and 24-hour ambulatory BP monitoring (ABPM) were evaluated initially and in 12 months of antihypertensive therapy. Results. Significant decrease of clinical BP was observed in 12 months of therapy in all patients. Target BP level was reached in 37 % of patients. ABPM indices were also improved: average BP levels and hypertensive burden time decreased, speed of morning BP raise was slow down, there was a tendency to 24-hour BP rhythm improvement. Tolerability of combined therapy was good. Conclusion. The combined antihypertensive therapy based on ramipril, metoprolol tartrate, amlodipine bensilate, rilmenidine dihydrogen phosphate showed good efficacy and safety in hypertensive patients with CGN and normal renal function.